Characterization by PCR-RFLP of the Cryptococcus neoformans and Cryptococcus gattii species complex in Venezuela - Ferrara, Giuseppe; Panizo, María Mercedes; Urdaneta, Emilia; Alarcón, Victor; García, Nataly; Moreno, Xiomara; Capote, Ana María; Reviakina, Vera; Dolande, Maribel (Investigación Clínica, 2018)
Abstract. Cryptococcosis is a sub-acute or chronic mycosis caused by opportunistic yeasts of the Cryptococcus genus, mainly by the C. neoformans and C.gattii species complex. This disease tends to position itself as one of the first opportunistic conditions associated with AIDS, with a high morbidity in these patients, who frequently develop meningoencephalitis. To date, there are techniques that allow the identification of the eight molecular types associated with these species complex, but there is little information about their circulation in Venezuela. The purpose of this work was to perform the molecular characterization of the C. neoformans and C.gattii species complex by PCR-RFLP. A total of 80 strains were used, 65 of the C. neoformans complex (CNC) and 15 of the C. gattii complex (CGC), following the protocol described by Escandon et al., carrying out the amplification of the URA5 gene and subsequent digestion with the Sau96I and HhaI restriction enzymes, that generated band patterns that allowed the identification of different molecular types. The most prevalent molecular type was VNI with 68.75% (n=55), similar to that reported worldwide;secondly, VGII molecular type with con 15% (n=12), which corresponds to that reported for Latin America, followed by VNII with 11.25% (n=9), VGIII with 2.5% (n=2), VNIII with 1.25% (n=1) and VGI with 1.25% (n=1)). Ninety-two point three percent of CCN (n=60) and 66.7% (n=10) of GCC isolates were from patients with HIV/AIDS. This study provided important epidemiological information on circulating molecular types and allowed to deepen the knowledge of this opportunistic mycosis in Venezuela.